Approximated Methods for Linear Delay Differential Equations Using Weighted Residual Methods (Baghdad Science Journal, 2025)
The main work of this paper is devoted to a new technique of constructing approximated solutions for linear delay differential equations using the basis functions power series functions with the aid of Weighted residual methods (collocations method, Galerkin’s method and least square method).